ON THE DARK SIDE OF LEARNING CALCULUS: EVIDENCE FROM AGRIBUSINESS STUDENTS - Leomarich F Casinillo; Ginna F Tavera (IJIET (International Journal of Indonesian Education and Teaching), 2021)
This study focused on evaluating the agribusiness students’ negative experiences in learning Calculus. The study employed 121 agribusiness students in the first semester of the school year 2019-2020 at Visayas State University, Baybay City, Leyte, Philippines. Selected secondary data from the study of Casinillo and Casinillo (2020a) was utilized in this study. With the aid of a correlational research approach, this study stresses to explain the nature and characteristics of negative effects of learning calculus which is very helpful for improving the level of achievement of students and modifying the strategy of mathematics teachers. Results showed that most of the agribusiness students don’t have enough background in pre-calculus topics since there are only 9% of them took a STEM strand during senior high school. Seemingly, it is revealed that students are experiencing extreme stress, natural emotional exhaustion and frustration, and average absenteeism, somatic burden, and laziness in learning Calculus. It is found out that the negative experiences of these agribusiness students are significantly related to each other. This suggests that these negative experiences are inter-correlated and dependent on each other which is wearisome to their studies and leads to poor academic performance. However, these students are driven to pursue studying calculus since it's part of their requirements in their degree program. Hence, by proper motivation and appropriate teaching strategy in Calculus, these students can progress their level of achievement.